Utilization of Papaya Waste as Dairy Cattle Feed on Fermentability Value (In Vitro) - Nurjannah, Syifa; Suryanah, Sari (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Papaya is a plant that is commonly found in Indonesia, especially on the island of Java. The waste produced in the form of peel, seeds and leaves can be used as an alternative animal feed. The aims of the study was to utilize and evaluate papaya waste as dairy cattle feed. The research was carried out in two places, at the Laboratory of Ruminant Nutrition and Feed Chemistry, Faculty of Animal Husbandry Padjadjaran University and at the Service Laboratory of Pakuan University from September to October 2021. The research method used was Completely Randomized Design with seven treatments (P1: 100% Papaya peel, P2: 100% Papaya Seeds, P3: 100% Papaya leaves, P4: 50% Papaya peel and 50% seeds, P5: 50% Papaya peel and 50% leaves, P6: 50% Papaya seeds and 50% leaves, P7: 33,33% Papaya peel, 33,33% seeds, and 33,33% leaves), each treatment was repeated four times. The research were tested in vitro. The used medium was McDougall fluid and rumen of dairy cattle. The data obtained were analyzed by ANOVA using SPSS 20 software and Duncan's Multiple Range Test. The variables observed were feed fermentability values (VFA, NH3, and pH). The results showed that the utilization of papaya waste significantly (P<0.05) affected to the production of VFA, and NH3, pH with an average of 98.17-194.42 mM, 3.48-7.10 mM, and 6.87-7.04. In conclusion, the utilization of papaya waste mixed with peel and leaves showed the best results.